PENGENALAN MANAJEMEN BISNIS SYARIAH MELALUI PELATIHAN DIGITAL MARKETING USAHA MIKRO KECIL DAN MENENGAH DI DESA GUNUNG BUNDER II, KECAMATAN PAMIJAHAN, KABUPATEN BOGOR - Trisia Amalia; Rully Trihantana; Ermi Suryani (SAHID EMPOWERMENT JOURNAL, 2021)
Abstract The Covid-19 virus has appeared in Indonesia since March 2020, the existence of this covid virus has a major impact on MSME actors, especially in Gunung Bunder 2 Village, Pamijahan District, Bogor Regency. Gunung Bunder 2 Village is one of the tourist villages and includes a productive community because in that village there is an Aquascape MSME. These aquascapes are types of decoration for the aquarium. And to minimize the impact of covid-19 on the Aquascape MSMEs, I conducted socialization to the surrounding community, especially the Aquascape MSME actors about the importance of the Digital Marketing strategy and created Instagram, Facebook, and WhatsApp Business accounts that would help as a marketing medium for Aquascape products. With this technology-based marketing, I hope that the sale of various types of Aquascape products can be sold maximally because the use of the internet, especially social media, is more effective and reaches all levels of society. Especially during the Covid-19 pandemic, everyone spends time on the internet and conducts buying and selling activities online, especially through social media and e-commerce. Keyword: Digital Marketing, MSME Aquascape, Covid-19